2016
DOI: 10.1186/s12882-016-0334-3
|View full text |Cite|
|
Sign up to set email alerts
|

Chloride content of solutions used for regional citrate anticoagulation might be responsible for blunting correction of metabolic acidosis during continuous veno-venous hemofiltration

Abstract: BackgroundCitrate, the currently preferred anticoagulant for continuous veno-venous hemofiltration (CVVH), may influence acid-base equilibrium.MethodsThe effect of 2 different citrate solutions on acid-base status was assessed according to the Stewart-Figge approach in two consecutive cohorts of critically ill adult patients. The first group received Prismocitrate 10/2 (PC10/2; 10 mmol citrate/L). The next group was treated with Prismocitrate 18/0 (PC18; 18 mmol citrate/L). Both groups received bicarbonate-buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In contrast to our results, Khadzhynov and others found that the bicarbonate concentration and base excess were below the normal ranges (69.9% and 84.6%, respectively) during RCA haemodiafiltration. Jacobs et al reported metabolic alkalosis (pH >7.5) in 10% of patients treated with pre-dilution CVVH RCA in the group of patients treated with Prismocitrate 18 solution in contrast to its absence in patients treated with Prismocitrate 10/2 solution (Jacobs et al, 2016). Since our data collection, the protocol recommended by Nikkiso changed the starting dose from 35 ml/kg/h to 25 ml/kg/h, which results in decreased citrate dose and might lead to lower incidence of both metabolic alkalosis and hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, Khadzhynov and others found that the bicarbonate concentration and base excess were below the normal ranges (69.9% and 84.6%, respectively) during RCA haemodiafiltration. Jacobs et al reported metabolic alkalosis (pH >7.5) in 10% of patients treated with pre-dilution CVVH RCA in the group of patients treated with Prismocitrate 18 solution in contrast to its absence in patients treated with Prismocitrate 10/2 solution (Jacobs et al, 2016). Since our data collection, the protocol recommended by Nikkiso changed the starting dose from 35 ml/kg/h to 25 ml/kg/h, which results in decreased citrate dose and might lead to lower incidence of both metabolic alkalosis and hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…As also reported in previous studies, the results of our study indicated that most speci c RCA protocols can cause upward or downward trends in bicarbonate concentrations and base excess. Jacobs et al reported metabolic alkalosis (pH > 7.5) in 10% of patients treated with pre-dilution CVVH RCA in the group of patients treated with Prismocitrate 18 solution in contrast to its absence in patients treated with Prismocitrate 10/2 solution [29].…”
Section: Ph and Bicarbonatementioning
confidence: 98%
“…Yet, the C18 solution contained more sodium (152 vs.143 mmol/l), resulting in higher sodium levels throughout the study. This relative 'hypernatremia' significantly increased SIDa uncovering metabolic alkalosis [2,5,7] . Counteracting metabolic alkalosis thus depends on the inciting culprit.…”
mentioning
confidence: 99%
“…Metabolic alkalosis, however, may also be related to the electrolyte composition of the chosen citrate liquids. Patients who received C18 in the Jacobs et al [7] study developed hypochloremic metabolic alkalosis, which stemmed from the lower chloride content of the C18 as compared with the C10/2 solution (86 vs. 106 mmol/l). In the BEaRRS study, the 2 studied citrate solutions had similar chloride content (99 mmol/l).…”
mentioning
confidence: 99%
See 1 more Smart Citation